RELATIONSHIP BETWEEN MENSTRUATION PHASE AND FATAL SELF-DIRECTED VIOLENCE AMONG FEMALES OF THE REPRODUCTIVE AGE GROUP (Journal of Forensic Medicine & Toxicology, 2023)
Various studies have been done to determine the link between the menstrual cycle and suicidal behaviour. Young women are more vulnerable to suicide ideation. Due to hormonal factors, suicide attempts and suicidal ideations are at an all-time peak during menstruation. In this retrospective study, data were obtained from cases of suicide reported to the Department of Forensic Medicine & Toxicology over a period of 5 years from January 2014 to December 2018. A total of 4973 autopsies were conducted of which suicidal cases in reproductive age group contributed to 4.68% (233) of cases. In present study, 30.83% suicide cases are in menstruating phase. Maximum cases of menstruation were seen in 21-30 yrs age group and least cases were seen in 41-50 yrs age group. This study revealed that the majority of suicide done by women during their menstrual phase of the menstrual cycle when their estradiol and progesterone levels are the lowest.
Keywords: Menstruation; Suicide; Hanging; Poison